Post-traumatic stress disorder in a military cohort with war trauma - Alirio Bastidas Goyes (ECIMED, 2021)
Introduction: People who are part of the armed forces worldwide have been susceptible to the development of post-traumatic stress disorder, due to exposure to conditions that predispose its development. Objective: To establish the frequency and possible associated risk factors of post-traumatic stress disorder in subjects with chest injuries, suffered in combat. Methods: Comparative study between subjects with chest trauma suffered in combat and military without thoracic injury with experience in combat, by evaluating a 24-question diagnostic questionnaire, validated for Colombia, of post-traumatic stress disorder. Military population older than 18 years and younger than 55 years, with chest trauma who underwent medical or surgical management (thoracotomy or laparotomy) were included. Results: 45 subjects entered the study, 25 with a history of chest trauma and 20 healthy with combat experience. Of the trauma subjects, 25 were evaluated at 3 months and 11 at 5 months. In the subjects wounded in combat, the average age was 24,1 years (SD: 4,99). At the 3-month evaluation, 36 % (p = 0,025) of the subjects with a history of chest trauma met the diagnostic criteria for post-traumatic stress disorder, which shows an increase of 9,5 % at the 6-month follow-up. Conclusion: There is a higher frequency of post-traumatic stress disorder in subjects exposed to traumatic chest events in areas of armed conflict. Young age and low educational levels could be factors associated with the appearance of the disorder.